BPTF cooperates with p50 NF-κB to promote COX-2 expression and tumor cell growth in lung cancer - Dai, Meng (Am J Transl Res, 2019)
Cyclooxygenase-2 (COX-2) is overexpressed in most human cancers, but its precise regulatory mechanism in cancer cells remains unclear. The aims of this study are to discover and identify the new regulatory factors which bind to the COX-2 promoter and regulate COX-2 expression and cancer cell growth, and to elucidate the mechanisms of action of these factors in lung cancer. In this study, the COX-2 promoter-binding protein BPTF (bromodomain PHD finger transcription factor) was detected, identified and verified by biotin-streptavidin-agarose pulldown, mass spectrum analysis and chromatin immunoprecipitation (ChIP) in lung cancer cells, respectively. The expressions of COX-2 and BPTF in lung cancer cell lines, mouse tumor tissues and human clinical samples were detected by RT-PCR, Western blot and immunohistochemistry assays. The interaction of BPTF with NF-kB was analyzed by immunoprecipitation and confocal immunofluorescence assays. We discovered and identified BPTF as a new COX-2 promoter-binding protein in human lung cancer cells. Knockdown of BPTF inhibited COX-2 promoter activity and COX-2 expression in lung cancer cells in vitro and in vivo. We also found that BPTF functioned as a transcriptional regulator through its interaction with the p50 subunit of NF-kB. Knockdown of BPTF abrogated the binding of p50 to the COX-2 promoter, while the inhibition of p50 activity abolished the decreased trend of COX-2 expression and lung cancer cell proliferation caused by BPTF silencing. Moreover, we showed that the expressions of BPTF and COX-2 in tumor tissues of lung cancer patients were positively correlated, and high co-expression of BPTF and COX-2 predicted poor prognosis in lung cancer patients. Collectively, our results indicated that BPTF cooperated with p50 NF-κB to regulate COX-2 expression and lung cancer growth, suggesting that the BPTF/p50/COX-2 axis could be a potential therapeutic target for lung cancer.